Dampak Pendidikan Inklusif Terhadap Siswa Dengan Kebutuhan Khusus - Agustina Purnami Setiawi; Yulius Keremata Lede; Yuliana Sesi Bitu; Samuel Rex Mulyadi Making; Elyakim Nova Supriyedi Patty (Journal on Education, 2024)
This article aims to explore and analyze the impact of inclusive education on students with special needs. Involving a qualitative approach, the research focused on the learning experiences, social interactions and academic development of students involved in inclusive education. Key findings include increased social engagement, motivation and participation, along with positive academic development. Support from inclusive teachers and classmates played a key role in overcoming potential social isolation and building students' self-confidence and motivation. This research provides an in-depth understanding of the role of inclusivity in creating an equal, meaningful and enriching educational environment for students with special needs. The implications and recommendations of this research can support the development of more effective inclusive education policies and strengthen support for students with special needs.